The risk of thyroid cancer after hysterectomy and oophorectomy: a meta-analysis - Fu, Shenguang; Lu, Yiping; Liu, Yibo (Frontiers in Oncology, 2024)
ObjectivesThe purpose of this meta-analysis is to assess whether there is an association between hysterectomy and oophorectomy and risk of primary thyroid cancer.MethodsPubMed, Cochrane Library, Embase, and Web of Science were searched for eligible studies published from database inception to May 13, 2024, using medical subject headings (MeSH) and keywords. All statistical analyses were performed using Stata statistical software (version 14.0). If P > 0.1 and I2 ≤ 50%, a fixed-effects model was adopted. If I2 > 50% a random-effects model was adopted. The funnel plot and Egger’s test were used to evaluate publication bias.ResultsA total of 11 studies explored the association between a history of hysterectomy, oophorectomy and the risk of thyroid cancer. The pooling analysis shows that a history of hysterectomy, oophorectomy is associated with an increased risk of thyroid cancer (HR = 1.597; 95% CI: 1.467-1.738; I2 = 57.1%, P = 0.01 < 0.1). In the subgroup analysis, a follow-up duration exceeding 20 years is linked to an elevated risk of thyroid cancer (HR = 1.772; 95% CI: 1.301-2.414; I² = 81.70%, P = 0.004 > 0.001). Hysterectomy combined with salpingo-oophorectomy is associated with a higher risk of thyroid cancer incidence (HR = 1.633; 95% CI: 1.449-1.841; I² = 51.10%, P = 0.069 > 0.001). Studies that balanced smoking, alcohol consumption, and history of thyroid disease demonstrated an association between hysterectomy and increased risk of thyroid disease (HR = 1.734; 95% CI: 1.591-1.891; I² = 31.30%, P = 0.225 > 0.001).ConclusionsOur meta-analysis reveals a heightened risk of primary thyroid cancer following hysterectomy and oophorectomy. These findings underscore the importance of considering potential cancer risks when determining surgical approaches and implementing preventive measures prior to these procedures.The meta-analysis was conducted in adherence to the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) (1). The protocol was pre-registered on the International Prospective Register of Systematic Reviews (PROSPERO) platform, with the registration number CRD42024546451.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier CRD42024546451.